2021
DOI: 10.1002/aelm.202100650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humidity on the Writing Speed and Domain Wall Dynamics of Ferroelectric Domains

Abstract: The switching dynamics of ferroelectric polarization under electric fields depends on the availability of screening charges in order to stabilize the switched polarization. In ferroelectrics, thin films with exposed surfaces investigated by piezoresponse force microscopy (PFM), the main source of external screening charges is the atmosphere and the water neck, and therefore relative humidity (RH) plays a major role. Here, it is shown how the dynamic writing of domains in BaTiO3 thin films changes by varying sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Other known active species include carbonated organic molecules, with different carboxylic groups and Si oxides, or other salts formed from ions contained in the material. So far, the race towards understanding the interplay between ferroelectricity and surface electrochemistry still faces crucial unresolved issues, since at the nanoscale the ferroelectric state is fundamentally inseparable from the electrochemical state of the surface (Yang, Morozovska et al, 2017) and determines ferroelectric switching dynamics (Spasojevic, Verdaguer et al, 2022). This coupling has strong impact on the application of ferroelectric materials in nanodevices such as Tunnel Junctions (Lu, Lipatov et al, 2014;Guo, Wang et al, 2017) since it can create an imprint in the ferroelectric state (Lee, Kim et al, 2016) or alter associated fundamental physical properties such as tunnelling eletroresistance (Gruverman, Wu et al, 2009).…”
Section: Ferrocatalysis and Switchable Catalysismentioning
confidence: 99%
“…Other known active species include carbonated organic molecules, with different carboxylic groups and Si oxides, or other salts formed from ions contained in the material. So far, the race towards understanding the interplay between ferroelectricity and surface electrochemistry still faces crucial unresolved issues, since at the nanoscale the ferroelectric state is fundamentally inseparable from the electrochemical state of the surface (Yang, Morozovska et al, 2017) and determines ferroelectric switching dynamics (Spasojevic, Verdaguer et al, 2022). This coupling has strong impact on the application of ferroelectric materials in nanodevices such as Tunnel Junctions (Lu, Lipatov et al, 2014;Guo, Wang et al, 2017) since it can create an imprint in the ferroelectric state (Lee, Kim et al, 2016) or alter associated fundamental physical properties such as tunnelling eletroresistance (Gruverman, Wu et al, 2009).…”
Section: Ferrocatalysis and Switchable Catalysismentioning
confidence: 99%
“…As shown in Figure 3d, the threshold voltages were dependent on the writing-speeds, namely the threshold voltage increasing as a function of the writing speed (Figure S7, Supporting Information). This phenomenon can be explained by insufficient surface screening charges capable of stabilizing the newly formed domains at high writing-speed, [21,33] resulting in a system requiring more energy when switched from one state to another. [34] These results were similar to the speeddependent domain wall widths [21] and the simulated electric field distribution under the tip bias.…”
Section: Critical Voltages/forces For Domain Switching At Different T...mentioning
confidence: 99%
“…This phenomenon can be explained by insufficient surface screening charges capable of stabilizing the newly formed domains at high writing-speed, [21,33] resulting in a system requiring more energy when switched from one state to another. [34] These results were similar to the speeddependent domain wall widths [21] and the simulated electric field distribution under the tip bias. [35][36][37] Thus, successful domain writing with increased speed required a higher PFM tip voltage.…”
Section: Critical Voltages/forces For Domain Switching At Different T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Spasojevic et al showed that the humidity condition plays a crucial role in determining the polarization switching dynamics of ferroelectric materials. [258] Their PFM studies revealed that the speed for domain writing on the surface of BaTiO 3 thin films increased non-monotonically with humidity. For a particular writing speed, the size of the written domains was found to follow water adsorption behavior.…”
Section: Surface Protonation and Deprotonationmentioning
confidence: 99%